Bariery dyfuzji wiedzy w przedsiębiorstwach - Perechuda, Kazimierz (Barriers of the Knowledge Diffusion in Companies, 2005)
The paper presents:- the barriers of the knowledge implementation,- the role of the knowledge workers in the knowledge diffusion in the net enterprise..
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 226-230